Growing Intimate With Monsters: Shelley Jackson’s Patchwork Girl and the Gothic Nature of Hypertext - Keep, Christopher (Romanticism on the Net, 2006)
AbstractDescribed by Robert Coover as “perhaps the true paradigmatic work” of the “golden age” of hypertext literature, Shelley Jackson’s Patchwork Girl (1995) provides not only a rewriting of Mary Shelley’s Frankenstein (1818), but an opportunity to consider the ways in which the gothic as a genre serves to problematize the somatic dimension of our writing technologies. In its capacity to touch the reader directly, at the level of the nerves, tissues, and fibres of the body, Patchwork Girl recalls the debates concerning the affective force of the gothic novel, and, in particular, the threat it was thought to pose for women readers. The gothic, in this sense, emerges as the deep and unsettling recognition that the technological is the formative ground of subjectivity, the very condition of our becoming. What Jackson calls “the banished body,” the monstrous materiality of subjectivity, haunts not only the eighteenth-century faith in the powers of rational powers of intellection, but our own post-human dreams of transcendence.